چائلڈ میرج کی ممانعت: وفاقی شرعی عدالت کے دلائل کا تجزیاتی مطالعہ: The Prohibition of Child Marriage: An Analytical Study of the Arguments of the Federal Sharia Court - Abdul Majeed (AL-IDRAK JOURNAL, 2023)
The role of the Federal Sharia Court in the history of Islamization of laws in Pakistan is very important. The Federal Shariah Court has not only played an important role in Islamizing the laws but also has been a key position of the respected court in interpreting the Islamic laws and making them compatible with the society. The minimum age for a girl to marry in Pakistan is sixteen years. The marriage of a girl below this age is prohibited by law. Scholars in this matter are divided into two classes. One side insists on calling it a purely religious issue while the other side considers it a purely social issue. The decision of the Federal Sharia Court on this case was issued some time ago. This decision has given a new dimension to academic research. In this decision, the honorable court, reasoning from the basic principles of Islamic jurisprudence, has declared the law of prohibition of child marriage prevalent in Pakistan to be in accordance with Sharia. In this paper, the arguments established by the honorable court will be analyzed and an attempt will be made to find out on what grounds the reasoning of the court is based. To what extent is the dimension considered by the court's reasoning correct? Is the argument made by the court logical? Is there mutual uniformity in the reasoning of the court and the conclusion drawn from it? Also, these issues will be marked in the paper which can be used as a basis to move towards the solution of this problem.